Regional Economic Outlook, November 2013, Middle East and Central Asia. (Regional Economic Outlook, 2013)
The November 2013 Regional Economic Outlook: Middle East and Central Asia reports the near-term economic outlook for the Middle East region has weakened. Difficult political transitions and increased regional uncertainties weigh on confidence in the oil-importing countries. Growth in these countries remains well below the levels necessary to reduce high unemployment and improve living standards. Meanwhile, in the oil-exporting countries, weak global demand and domestic supply disruptions have reduced oil production, notwithstanding recent upward pressure arising from increased geopolitical risks. Medium-term economic prospects are clouded by rising fiscal vulnerabilities, declining productivity, and fragmented labor markets. Although economic activity in the Caucasus and Central Asia continues to expand at a fast pace, risks are also on the rise, including a further slowdown in Russia and China and unaddressed structural impediments.